Toward Comprehensive Plant Microbiome Research - Saikkonen, Kari; Nissinen, Riitta; Helander, Marjo (Frontiers in Ecology and Evolution, 2020)
Microbes have driven eco-evolutionary adaptations organizing biodiversity from the origin of life. They are ubiquitous and abundant, facilitating the biochemical processes that make Earth habitable and shape ecosystem structures, functions, and services. Recent studies reveal that commensalistic and beneficial microbes associated with wild and domesticated plants may aid in establishing sustainable agriculture for a changing climate. However, developing microbe-based biotechnologies and ecosystem services requires a thorough understanding of the diversity and complexity of microbial interactions with each other and with higher organisms. We discuss the hot and blind spots in contemporary research on plant microbiomes, and how the latest molecular biological technique and empirical eco-evolutionary approaches could elevate our perception of microbe–plant interactions through multidisciplinary approaches.